The Relationship Between Childhood Adversity and Other Aspects of Clinical Complexity in Psychiatric Outpatients - Maunder, Robert G. (Journal of interpersonal violence, 2021)
Childhood abuse, neglect, and loss are common in psychiatric patients, and the relationship between childhood adversity and adult mental illness is well known. However, beyond diagnoses that are specifically trauma-related, such as posttraumatic stress disorder, there has been little research on how childhood adversity contributes to complex presentations that require more intensive treatment. We examined the relationship between childhood adversity and other contributors to clinical complexity in adult outpatients seeking mental health assessment. In a cross-sectional study, patients completed standard measures of psychological distress and functional impairment. Psychiatrists completed an inventory of clinical complexity, which included childhood abuse, neglect, and loss. Of 4,903 patients seen over 15 months, 1,315 (27%) both consented to research and had the measure of complexity completed. Childhood abuse or neglect was identified in 474 (36.0%) and significant childhood loss in 236 (17.9%). Correcting for multiple comparisons and controlling for psychiatric diagnosis, age, and sex, patients with childhood abuse or neglect were significantly more likely to also have 11 of 31 other indices of clinical complexity, with odds ratios ranging from 1.7 to 5.0. Both childhood abuse or neglect and childhood loss were associated with greater overall complexity (i.e., more indices of complexity, χ2 = 136 and 38 respectively, each p < .001). Childhood abuse and neglect (but not childhood loss) were significantly associated with psychological distress (Kessler Psychological Distress Scale [K10] score, F = 6.2, p = .01) and disability (World Health Organization Disability Assessment Scale 2.0 [WHODAS 2.0] score, F = 5.0, p = .03). Childhood abuse and neglect were associated with many characteristics that contribute to clinical complexity, and thus to suboptimal outcomes to standard, guideline-based care. Screening may alert psychiatrists to the need for intensive, patient-centered, and trauma-informed treatments. Identifying childhood adversity as a common antecedent of complexity may facilitate developing transdiagnostic programs that specifically target sources of complexity.